Nihongo Application For Android Mobile Phone - Abas, Novel Idris, Husni Thamrin, S.T, M.T, Ph.D, Aris Rakhmadi, S.T., M. Eng (2013)
Japan is an interesting country in many aspects. Most people, especially those who first come to Japan face problems. The problems include the difference of language. Nihongo, is a unique language. It has special structure of the sentence. In this research we develop Nihongo application which has focus two focuses, i.e. to ease Indonesian to communicate in Japanese language, and give some short information about Japan. Fix and Code Software development model is used to develop the application. The Nihongo application has features Hiragana table, Katakana table, daily conversations in Bahasa, Romaji, and Nihongo translation, video about Japan, top cities in Japan with its attractions, tips about staying in Japan, more than 2.000 vocabularies in Bahasa, Romaji, and Nihongo translation, and short information about Nihongo application. The application can be installed at Android Froyo OS (2.2) or later. The application is tested on Smartfren Andromax i, Sony Experia Miro, Samsung Galaxy mini 2, Samsung Galaxy S2, Samsung Galaxy W, Sony Ericsson Mini Pro, and Samsung Galaxy Ace 2. The result of the test proves that the Nihongo application run well. Our surveys say that the application clearly gives useful information about Japan, and eases Indonesian to communicate, socialize, and live in Japan.